Ruling reasons: a defense of constructivism about reasons and objectivism about welfare - Fan, Z (2021)
I argue in this thesis in favor of a position that combines constructivism about reasons and objectivism about welfare. In Chapter 1, I define reasons constructivism, on the basis of the Kantian origin of the view. I argue that reasons constructivism is a claim about the perspective-relativity of normative reasons for action. Furthermore, I argue that reasons constructivism, as I define the view, is distinct from both reasons objectivism and reasons subjectivism. In Chapters 2 and 3, I offer an argument in favor of reasons constructivism. I argue that in interpersonal reasoning, one agent can only offer reasons to another by engaging in the “if I were you” mode of reasoning. I show that these considerations support reasons constructivism, rather than other meta-ethical views about reasons. Finally, in Chapter 4, I argue that reasons constructivism can be combined with welfare objectivism. I show that this approach allows constructivists to generate the right reasons for agents with fundamentally corrupt judgments. Furthermore, I argue that this mixed position is coherent.